Angiographic Embolization of a Postpartum Vulvovaginal Hematoma in a Patient with Situs Inversus Totalis: An Effective Second-Line Treatment - Elias M. Dahdouh; Jacques Balayla; Johanne Dubé (Hindawi Limited, 2013)
Situs inversus totalis is a rare congenital anomaly where asymmetrical positioning of internal organs may affect the surgical and radiological management of certain conditions. Vulvovaginal hematoma is a life-threatening complication of vaginal delivery whose primary treatment usually consists of incision and drainage of the hematoma and ligation of the responsible vessels, followed by wound packing. Failure of these measures to control the bleeding was previously considered as an indication for laparotomy to perform bilateral hypogastric artery ligation and, if needed, a hysterectomy. Relative to major abdominal surgery, selective percutaneous angiographic embolization offers considerable advantages and significant less morbidity. Indeed, angiographic embolization is routinely used as a measure to control refractory pelvic bleeding, though the literature and experience in women with situs inversus totalis are scarce. In this paper, we report a case of postpartum vulvovaginal hematoma in a patient with situs inversus, refractory to conventional treatment, where arteriographic embolization was successfully used to control the bleeding. The management of this obstetrical complication and the use of this minimally invasive technique are also reviewed. To the best of our knowledge, this is the first report in the literature describing the feasibility of this technique in a patient with situs inversus totalis.